2023
DOI: 10.1177/11795735231156349
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen as a Predictor of Early Neurological Deterioration in Acute Ischemic Stroke – Evidence From the Indian Population

Abstract: Background Early neurological deterioration (END) is a common occurrence in ischemic stroke and contributes significantly to poor outcomes. Although multiple factors that predict END have already been identified, the role of fibrinogen – a key component of the coagulation pathway, is controversial. Objective To assess the role of fibrinogen in predicting END and poor hospital outcome in patients with acute ischemic stroke. Design Single-centre prospective observational study. Methods 141 patients with acute is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…A study using data from China’s National Stroke Registry III, which included 10,518 patients with AIS within seven days of onset (baseline), showed that high baseline fibrinogen levels were associated with poor functional prognosis (mRs > 2) (OR = 1.63; 95%=CI:1.35–1.97) [ 41 ]. Similar results were obtained in a small-sample study from India, where baseline fibrinogen (per 1 mg/dL) was positively associated with poor functional prognosis (OR = 1.011, 95% CI 1.006–1.015, P < 0.001) [ 18 ]. However, some studies have yielded inconsistent results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A study using data from China’s National Stroke Registry III, which included 10,518 patients with AIS within seven days of onset (baseline), showed that high baseline fibrinogen levels were associated with poor functional prognosis (mRs > 2) (OR = 1.63; 95%=CI:1.35–1.97) [ 41 ]. Similar results were obtained in a small-sample study from India, where baseline fibrinogen (per 1 mg/dL) was positively associated with poor functional prognosis (OR = 1.011, 95% CI 1.006–1.015, P < 0.001) [ 18 ]. However, some studies have yielded inconsistent results.…”
Section: Discussionsupporting
confidence: 84%
“…One study confirmed that hyperfibrinogenemia (> 4.0 g/L) is associated with a 1.76-fold increase in the risk of in-hospital mortality (hazard ratio, HR = 1.76; 95% confidence interval [CI]: 1.10–2.81), but found no significant association with poor prognosis at discharge (mRS > 3) [ 17 ]. A study from India demonstrated through regression analysis that fibrinogen levels (mg/dl) were positively correlated with early neurological deterioration (OR = 1.004, 95% CI 1.000-1.007, P = 0.038) [ 18 ]. Another study showed that after adjusting for potential confounders, the relationship between fibrinogen levels and poor outcomes after AIS (mRS > 3) was not significant (OR = 1.05, 95% CI: 0.90–1.21) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, elevated fibrinogen levels serve as an autonomous risk factor for both venous and arterial clotting, correlating with a more intense progression and poorer prognosis [27][28][29][30]. According to some authors, hyperfibrinogenemia is positively correlated with the type of infarction and the presence of ischemic lesions in the CT findings of cerebral ischemia [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, elevated fibrinogen levels serve as an autonomous risk factor for both venous and arterial clotting, correlating with a more intense progression and poorer prognosis [27][28][29][30]. According to some authors, hyperfibrinogenemia is positively correlated with the type of infarction and the presence of ischemic lesions in the CT findings of cerebral ischemia [29,30]. Peycheva et al [31] discovered that individuals with atherothrombotic stroke exhibited higher average fibrinogen levels (>4.0 g/l) in comparison to those with different stroke subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant relationship between fibrinogen levels and neurological deficit. In turn, Mehta et al [16] showed that the National Institutes of Health Stroke Scale score at admission (Odds Ratio (OR) 1.152 [95% CI 1.070-1.240], p<0.001), age (OR) 1.034 [95% CI 1.001- An increase in the level of fibrinogen is associated with an increased risk of ischemic stroke, and according to recent reports -also haemorrhagic. Sturgeon et al [14] prove that high levels of fibrinogen increase the risk of CNS bleeding.…”
Section: Discussionmentioning
confidence: 99%